Desenvolvimento e caracterização de copolímeros obtidos a partir de monômeros acrílicos e metacrílicos visando a aplicação como excipientes farmacêuticos para preparação de matrizes inertes por compressão direta - Janaina Cecilia Oliveira Villanova (2011)
Modified release tablets can improve patient compliance and provide extended periods of effective drug blood levels. The development of new materials for matrix forming tablets formulations has become more important recently and polymers and their blends can be used to achieve sustained release. Most investigated synthetic polymers used in the preparation of modified release tablets are based on acrylic and methacrylic monomers. Such versatile molecules are highly reactive and are able to interact among themselves and with other molecules, including natural macromolecules, enabling the control of chemical and physical properties of polymers according to the specific application. In this view, the objective of this work was to prepare copolymers obtained by suspension and emulsion polymerization process to be applied as a release controlling excipient in matrix tablets using direct compression. After synthesis, the copolymers were characterized by spectrophotometric methods and thermal analysis. Later, physical pharmaceutical assays, named micromeritics tests, were performed in order to study the suitability of the solid particles to be used as pharmaceutical excipient. Were investigated the morphology, granulometry assays, Hausner ratio, Carrs index and cotangent of angle. Moreover, preliminary in vitro cytotoxicity assessment was made using MTT assay. Finally the excipients containing cellulose nanowhiskers (named beads CNWB), beads containing low-methoxyl pectin chemically modified by glycidyl methacrylate (PECB) and lyophilized copolymers A and B were used to prepare matrix tablets by direct compression with propranolol hydrochloride (PHCl) as model drug. The release was studied according to dissolution profiles based on the methodology adapted from the United States Pharmacopeia 32th edition. The excipients prepared in the form of beads showed good flow and compressibility properties when compared with the copolymers lyofilized (A and B). The compression time, the type and amount of polymer used influenced the hardness and drug release. The dissolution profiles showed that the proposed excipient performed with 64%w/w of CNWB, 48%w/w of PECB and 64%w/w PECB formed inert matrices that would not erode and released the PHCl for a period exceeding 12 hours. For elucidation of the drug release mechanism, dissolution data was analyzed using Zero-order, First-order, Korsmeyer-Peppas and Higuchi equations, with linear regression. The models that best fits the release was found Higuchi and Korsmeyer-Peppas, which indicates the diffusion as the main drug release mechanism. The hardness of the tablets ranged from 41N to 184.5N, indicating that the tablets with higher hardness may be more compact and less porosity, resulting in slower release. Friability showed variation of results lower than 0.5% and the variation of the average weight was between ±10.0%. Finally, the results of the viability test indicated that acrylic copolymers are nontoxic and they are expected to be biocompatible for pharmaceutical applications